Jurisprudential and Legal Analysis of the Terminator’s Condition in Contract of the Endowment - Seyyed Mahdi Quraishi; Muhammad Hasan Javadi; Hamed Rahmani (آموزه‌‌های فقه مدني)
There is no specific comment in jurisprudence regarding the validity or voidness of the endowment that is conditioned by the terminator, but the jurists have provided different opinions about veracity and invalidity endowment contract and entailment in the case that the founder of an endowment has conditioned that it is returned to him when he is in need of endowed property. Since finding the right point in this regard has a direct effect on finding the answer to the fundamental question, this research by studying the jurisprudential ideas, has attempted to prove the correctness of the “endowment that is conditioned to return the endowed property to the founder of endowment in the case of need”. By examining the concept of the condition of the terminator in law, it will be consistent to the condition that is mentioned in the contract and it is possible to place the condition of the terminator in the contract of endowment and the condition of “returning of the endowed property to the founder of endowment in the case of need” is one of its clear example.